Early outcomes after TAPP vs. Lichtenstein repair: a prospective cohort from a resource limited surgical unit in South India - Loganathan, Peranbu; Kumar, Sailesh I. S.; Shantharam, Raja Vel; Rahuman, Ashfaq Sulaiman A. A.; N. Ramadas, Ashok; K. R. P., Viknesh (International Surgery Journal, 2025)
Background: Inguinal hernia repair is a globally prevalent surgical procedure. Despite declining age-standardized prevalence, the absolute global burden is increasing, necessitating optimized surgical strategies. Open Lichtenstein and laparoscopic (TAPP/TEP) mesh repairs represent the two dominant surgical approaches, each with distinct perioperative profiles and patient outcomes. This study prospectively compared these techniques to provide evidence-based guidance for surgical decision-making in resource-constrained healthcare settings. Methods: A prospective observational comparative study was conducted at a tertiary care teaching hospital in Chennai, India, between July 2022 to December 2023. Sixty eligible patients (59 male, 1 female; mean age ~45 years) with inguinal hernias were allocated to Lichtenstein open repair (n=30) or TAPP laparoscopic repair (n=30) based on clinical suitability patient factors, and surgeon discretion. Primary outcomes included operative time, postoperative pain (Visual Analog Scale-VAS at 12, 24, 48 hours), length of hospital stay, and time to return to work. Secondary outcomes were complications (infection, seroma, hematoma). Statistical analysis employed independent t-tests and chi-square/Fisher's exact tests (p<0.05 significant). Results: Operative time was significantly longer for TAPP (113.33±12.41 minutes) compared to Lichtenstein (61.50±11.23 minutes; p<0.001). However, the TAPP group demonstrated significantly lower VAS pain scores at 12 hours (4.83±0.70 vs. 7.60±0.77), 24 hours (2.97±0.72 vs. 5.03±0.85), and 48 hours (1.73±0.45 vs. 3.40±0.93; all p<0.001). Hospital stay was shorter for TAPP (4.97±0.85 days vs. 6.70±1.75 days; p<0.001), and return to work was faster (10.30±1.54 days vs. 18.50±2.80 days; p<0.001). Complication rates (infection, seroma, hematoma) were low and comparable between groups (infection: p=0.492; overall complications <5%). Direct hernias were more frequently repaired laparoscopically (p=0.042). Conclusion: While laparoscopic (TAPP) inguinal hernia repair requires significantly longer operative time and expertise, it offers substantial advantages in the early postoperative recovery, including reduced pain, shorter hospital stay, and faster return to normal activities, with equivalent safety profile compared to open Lichtenstein repair. These benefits support the role of laparoscopic repair, particularly in younger patients and when rapid functional recovery is prioritized, despite its technical demands.